2016
DOI: 10.3390/ijerph13100936
|View full text |Cite
|
Sign up to set email alerts
|

Menopausal Age and Chronic Diseases in Elderly Women: A Cross-Sectional Study in Northeast China

Abstract: Many factors affect menopausal age, and early or late onset of menopause may be associated with many chronic health problems. However, limited data are available regarding this phenomenon in the Northeast China population. For this study, 2011 elderly women were selected as a sample from participants in a cross-sectional survey performed using stratified, clustered multistage, and random sampling methods. Early menopause was more prevalent in subjects born from 1943 to 1947 (OR = 1.708, 95% CI = 1.205, 2.420) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
23
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 43 publications
6
23
0
2
Order By: Relevance
“…Consistent with previous studies showing that late menopause can increase the diabetes risk, the present findings also showed that the age at natural menopause affected type 2 diabetes risk even after adjustment for age, BMI and other potential confounders, though the cut‐off points for menopausal age differed from the previous studies. Another two studies involving menopausal age ≥53 years, which was in line with our cut‐off point for later age at menopause in the present study, showed that the association was not statistically significant after multivariable adjustment.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Consistent with previous studies showing that late menopause can increase the diabetes risk, the present findings also showed that the age at natural menopause affected type 2 diabetes risk even after adjustment for age, BMI and other potential confounders, though the cut‐off points for menopausal age differed from the previous studies. Another two studies involving menopausal age ≥53 years, which was in line with our cut‐off point for later age at menopause in the present study, showed that the association was not statistically significant after multivariable adjustment.…”
Section: Discussionsupporting
confidence: 91%
“…Both the European Prospective Investigation into Cancer and Nutrition (EPIC)-InterAct study in Europe 11 and Dongfeng-Tongji cohort study in China 12 have found that early menopause is associated with a greater risk of type 2 diabetes. Several other studies from the USA and China [13][14][15] reported that women with late menopause had an increased diabetes risk. Meanwhile, three studies from Italy, Japan and China found no effects of age at menopause on diabetes risk [16][17][18] .…”
Section: Introductionmentioning
confidence: 96%
“…The current study results revealed a signi cant increase in the incidence of diabetes, hypertension, cardiovascular diseases, and cervical cancer among the menopausal women. Similarly, Fu et al demonstrated a decline in the menopause age with the incidence of diabetes (36). Furthermore, the mean age at menopause decreased from 56.88 years in the 75-year age group to 40.16 years in the 35-year age group, representing a signi cant decrease in the mean age at menopause.…”
Section: Discussionmentioning
confidence: 80%
“…Cigarette smoking reduces the estrogen level and increases the androgen level, thereby decreasing the menopause age. Moreover, cigarette smoking has been mentioned to be a strong confounder due to its relationship with low BMI and early menopause (36).…”
Section: Discussionmentioning
confidence: 99%
“…GHQ-12 scores of four and above indicate a trend of psychological distress. 34,35 It is a brief, reliable, and valid instrument. The GHQ-12 has been validated in ESRD patients with good internal reliability and external validity in previous study.…”
Section: -Item General Health Questionnaire (Ghq-12)mentioning
confidence: 99%